Enhancing a Better Operation Management of Indonesian Toll Road - Karsaman, Rudy Hermawan; Weningtyas, Widyarini (International Journal of Economics and Financial Issues, 2015)
In line with Indonesian Government policy to develop toll road network extensively, the operation of existing toll road need to be improved to ensure a safety, smooth and efficient of toll traffic flow. One of its aspect related to toll operation and service system applied. Minimum service standard (MSS) are some parameters that adopted to measure the performance of toll road and consists of road condition, average traffic speed, accessibility, mobility, safety and support unit/emergency or accident response. To enhance the toll road service in Indonesia, the MSS need to be revised. The revision including improvement of values of indicators and their measurement methods as well as add some new substances and indicators. Expectation of increasing this MSS are to increase the quality and level of service of the toll roads, both in safety and comfort given to the user as well as consider the effect of the toll road to the environments surrounding. This paper describe the aspects that was considered in improving the MSS, both the parameters and its measurements, including their standard and references. Finally, the revision draft of MSS that proposed to be adopted by Ministry of Public Work is also presented. Keywords: Indonesian Toll Road Minimum Service Standard, Operation System, Accessibility, Mobility JEL Classifications: M000